LGG-06. CLINICAL FEATURES OF 1136 TUMORS OF CENTRAL NERVOUS SYSTEM IN CHILDREN: SINGLE INSTITUTIONAL REPORT FROM SHANGHAI XINHUA HOSPITAL, THE FOUNDING MEMBER OF CNOG. (23rd April 2019) - Han, Yipeng; Zhao, Yang; Jiang, Feng; Zhang, Chenran; Li, Qifeng; Wang, Baocheng; Ma, Jie
Abstract: BACKGROUND: Central nervous system (CNS) tumor is the most common solid neoplasm in children. Here we report clinical features of children with CNS tumor treated in our institute during recent 11 years. METHODS: Retrospective study was conducted in children with CNS tumor treated in Xinhua Hospital Affiliated to Shanghai Jiaotong University School of Medicine, during 2006 to 2017. Clinical data were collected. Statistical calculation was conduct for characteristic analyses. RESULTS: 1136 cases of CNS tumor in children were collected, with 712 males and 424 females. Age ranges were 9.33% in infants (< 1 y/o), 26.32% in toddler (1 - 3 y/o), 35.30% in preschool children (3 - 7 y/o), 27.11% in school-age children (7 - 15 y/o) and 1.94% in adolescence (> 15 y/o). 437 cases were diagnosed with WHO I-II grades and 392 cases were with WHO III-IV grades. There were 548 supratentorial tumors and 441 subtentorial tumors. The most common tumor type was medulloblastoma (n=168, 14.79%), followed by pilocytic astrocytoma (n=166, 14.61%). CONCLUSION: The gender ratios in different age ranges were stable, with high incidence in male than in female. In total, low grade tumors were more common than high grade tumors. Compare to our previous report, pilocytic astrocytoma was second most common tumor, following medulloblastoma.